Hur har införandet av automatiska mjölkningssystem påverkat juverhälsan hos mjölkkor och vilka riskfaktorer finns? - Jakobsson, Karin (2011)
Today, there are more than 12 000-14 000 farms worldwide using an automatic milking system (AMS). Studies have shown that transition to AMS affects the udder health of cows adversely, recognized primarily as elevated somatic cell counts. There are several reasons for this, for example the greater variation in milking frequency seen in AMS. On one hand, short milking intervals may lead to bad teat condition of the cows due to the stress the milking procedure exposes the teats to. Too long milking intervals, on the other hand, seem to predispose for milk leakage, which is, in turn, a risk factor for the development of mastitis. Moreover, the robot’s ability to clean the udder before milking has shown not to be satisfying, leading to poorer udder health and increased risk of invasion of pathogens into the udder. To optimize the udder health in herds with AMS, it is important to choose a system which enables guiding of the cow-traffic. The guidance needs to be individualized for each cow based on where in the lactation she is. Furthermore, preventive cleaning is of great importance to achieve good hygiene in barns and milking equipment.